FORMULATION AND IN VITRO TESTS OF KETOPROFEN NANOSUSPENSION USING THE MILLING METHOD WITH POLYMER VARIATIONS - HANUM, TENGKU ISMANELLY; PRASETYO, BAYU EKO; FADILLA, WAN (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this research was to formulate ketoprofen nanosuspension with a variety of polymers and to compare the dissolution rate of the nanosuspensions with ketoprofen suspension. Methods: Ketoprofen nanosuspension was formulated by milling method using a different polymer such as Polyvinyl Pyrrolidone (PVP) K-30 (F1), Polyvinyl Alcohol (PVA) (F2) and Hydroxy Propyl Methyl Cellulose (HPMC) (F3). Nanosuspensions were prepared and characterized, including organoleptic, pH, particle size, zeta potential, Polydispersity Index (PI), specific gravity, crystalline state determination, physical stability at room temperature for 3 mo, and in vitro dissolution test compared with ketoprofen suspension. Results: The ketoprofen nanosuspensions with PVP K-30 and PVA showed stable preparations, while those with HPMC showed less stability, as indicated by sedimentation during storage. The particle size values of PVP K-30 and PVA were 10.004±0.03 nm; and 9.560±0.01 nm; zeta potential and polydispersity index values met the test requirements. The dissolution rate of the ketoprofen nanosuspensions was higher with a cumulative of F1, F2, and F3 were 83.35%; 85.00%, and 81.09% after 60 min, while the ketoprofen suspension was only 7.62%. Conclusion: The milling method of ketoprofen nanosuspensions with PVP and PVA has more stable physical characteristics than nanosuspension with HPMC. The ketoprofen nanosuspensions have a higher dissolution rate than the ketoprofen suspension.